PERAN BUSINESS STRATEGICS DALAM MEMODERASI HUBUNGAN ANTARA INTELLECTUAL CAPITAL DAN FINANCIAL PERFORMANCE PADA PERUSAHAAN LQ 45 - Wiwik Anggraini; Amries Rusli Tanjung; Kamaliah Kamaliah (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2016)
The study is conducted with the purpose of acquiring empirical evidence relatedto the influence of intellectual capital (IC) in calculation of value added(VAICTM) and also each components of IC, there are capital employed efficiencyValue Added of Capital Employed (VACA), Value Added Human Capital (VAHU)and Structural Capital Value Added (STVA) toward the financial performance(ROA) of Business Strategics there are Asset Utilization Efficiency (AUE) andPremium Price Capability (PPC) as an moderating variable.The data used in this study were obtained financial data from the financialstatements of each company and a sample. The method of analysis is fixed effectanalysis using multiple regression with SPSS version 23. The population used inthis study is a LQ45 company listed on the Indonesia Stock Exchange in 2011-2015, with a total sample of 18 companies.Based on this research, it was found that the variable Value Added of CapitalEmployed (VACA) and Value Added Human Capital (VAHU) have a significanteffect on Return on Asset (ROA), while Structural Capital Value Added (STVA)has no significant effect on Return on Asset (ROA). The relationship ofIntellectual capital (VAICTM) variable have a significant effet on the Return onAsset (ROA) through Asset Utilization Efficiency (AUE) and Premium PriceCapability (PPC) as an moderating variable.